GERAKAN REVOLUSI HIJAU PESANTREN UNTUK MENCEGAH KERUSAKAN EKOLOGI - Ribut Baidi; Ahmad Ahmad; Moh. Soheh (Fakultas Agama Islam Universitas Islam Madura, 2023)
Ecological damage is a fundamental and widespread problem in Indonesia. This is due to environmental business activities carried out by individual and corporate investors. On the other hand, ecological damage is also caused by agricultural activities that are not environmentally friendly, such as the excessive use of fertilizers or chemicals to increase the productivity of agricultural products, as well as the use of springs through irrigation programs which actually kill the water sources themselves. Ecological damage will have an impact on the destruction of agricultural land and will lead to a potentially crucial food crisis in various regions, this is the reason for researchers to conduct this research. The research method in this research is qualitative with data collection techniques are interviews, observaation and documentation data analysis. The results showed that the problem of ecological damage directly opened Islamic boarding schools throughout contributed to initiating the green revolution as an environmentally friendly agricultural movement in order to prevent and anticipate environmental pollution and damage, as well as prevent the emergence of food crises due to damaged agricultural land. Islamic boarding schools, in this case, are required to apply Islamic religious concepts and teachings which not only lead to the strengthening of religious spirituality, social and human relations, but also play a role in protecting the environment as a relation of life. mankind. The research implications show that Islamic boarding schools should have more concern for ecology and green areas in Islamic boarding schools.